2015
DOI: 10.1016/j.tafmec.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

On the Line Method apparent fracture toughness evaluations: Experimental overview, validation and some consequences on fracture assessments

Abstract: This paper analyses the capacity of the Line Method to provide evaluations of the apparent fracture toughness, which is the fracture resistance exhibited by materials in notched conditions. With this aim, the experimental results obtained in 555 fracture tests are homogeneously presented and compared to the Line Method evaluations. It is remarked that the Line Method provides adequate estimates of the apparent fracture toughness, and also that it conveniently addresses the physics of the notch effect. All this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…With the aim of reducing the number of unsafe predictions when applying the notch correction in the FAD, the lower bound expression of the LM proposed in [41] will be used here. Equations (16) and (17) gather the notch correction and the corresponding K r correction, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the aim of reducing the number of unsafe predictions when applying the notch correction in the FAD, the lower bound expression of the LM proposed in [41] will be used here. Equations (16) and (17) gather the notch correction and the corresponding K r correction, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Equations (16) and (17) gather the notch correction and the corresponding K r correction, respectively. The "0.73" factor intends to capture the scatter observed in the fracture toughness results obtained in cracked conditions [41], intending to provide a 95% confidence level of the whole population of tests. This factor, together with the "20" factor inside the square root provide a lower estimate of the apparent fracture toughness results of the 555 tests used here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two criteria are the Theory of Critical Distances (TCD) [1][2][3][4][5][6][7][8] and the Strain Energy Density (SED) criterion [9][10][11][12][13][14][15][16][17]. The TCD has been successfully applied to polymers (e.g., [1,2]), metals (e.g., [2][3][4]), composites (e.g., [5]) and rocks (e.g., [6]), and has also been combined with Failure Assessment Diagrams in order to provide structural integrity assessment methodologies for structural components containing notches [7]. A comprehensive review of the TCD may be found in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Both of them (TCD and SED) have a linear-elastic nature and provide accurate predictions when analyzing fracture conditions in brittle materials. When applied in more ductile situations, the TCD may still be applied after a calibration process (e.g., [1,2,5]), while the SED criterion loses accuracy (e.g., [13,15,16]). …”
Section: Introductionmentioning
confidence: 99%